Establishment of highly efficient callus proliferation, plant regeneration and micro-tillering systems in commercial oat cultivars - Gharti-Chhetri, Gokarna; Olsson, Olof (MTT, 2004)
Different explants (seeds, mature embryos, 3-day and 6-day old leaf/mesocotyl joints) of seven commercial summer oat varieties (Adamo, Belinda, Birgitta, Freja, Matilda, Petra and Stork) and one winter line, Pen #65, were cultivated on 2, 4-D containing callus induction medium. After about 4 weeks, explants were evaluated for callus growth. In all varieties maximum callus growth was obtained from mature embryos. Efficient shoot regeneration could be obtained from Belinda (mature embryos, 3-day and 6- day old leaf/mesocotyl joints), Birgitta (3-day and 6-day old leaf/mesocotyl joints), Freja (seeds), Matilda (3-day old leaf/mesocotyl joints) and Stork (mature embryos, 3-day and 6-day old leaf/mesocotyl joints) and Pen #65 (3- day old leaf/mesocotyl joints) in a medium with a specific auxin/cytokinin combination. Plant regeneration occurred via either organogenesis or somatic embryogenesis. Root initiation and further growth took place in a hormone free medium. Cultivating 9-day old leaf/mesocotyl joints of winter oat varieties 83-48-CH and Gerald on 2,4-D and BAP containing MS2m medium suppressed apical growth and induced lateral enlargement of the apical domes. This led to the formation of multiple meristems and resulted in vigorous microtiller forming cultures. These oat tissue culture protocols have now established a base towards development of genetically engineered winter oat for Swedish conditions.
Keywords: Ka; tissue culture; winter oat; microtillering